Design and construction of a clay extruder for 3d printing (Revista Cientifica Ingenio Magno, 2021)
he objective of this research was to design and build a clay extruder for 3d printing, in response and as an alternative to the high costs presented by conventional materials (PLA, ABS). With this, the field of action of 3d printing would expand to other sectors of industry and crafts. The development of this article was divided into three phases: alternatives of mechanical systems were proposed, until reaching the optimal extruder model that meets the proposed objective. With the chosen model, a CAD (Computer Aided Design) dimensioning of the structure and subsystems was carried out. Then a simulation is carried out in CAE (Computer Aided Engineering) in order to find the critics of the extrusion process and finally the construction of the prototype is carried out.Two performance tests were carried out, one of semiautomatic control (manual nozzle displacement and controlled extrusion) and the other completely controlled with which the fulfillment of the functional and economic expectations was verified, reaching extrude a defined volume of material, however, it is impractical for the manufacture of large volume parts since it does not have a continuous material feed.
Keywords: 3d printing; clay; extruder; CAD; CAE; interchangeable nozzles